Invitro Determination Effectiveness of Acacia senegal and Juice of Actinidia deliciosa with Estimate Synergistic Effect Towards Some Pathogenic Bacteria of Human - Nayyef, Sura Hameed; Yaseen, Lina Qays; Wahab, Marwa Hasan Abdul (Journal for Research in Applied Sciences and Biotechnology, 2023)
Antimicrobial resistance is a real threat to human health in worldwide. One of these medicinal plants that are commonly used in addition to its source as food is also used as a treatment for some cases. Gum Arabic (GA) consider it protection against various bacterial infections. Kiwi fruit Commonly known as the, Actinidia deliciosa valuable medicinal properties such as its anti-inflammatory, anti-bacterial and anti-asthmatic efficacy. Gum Arabic in different concentrations (10,20,30 and 50)% also Actinidia deliciosa in concentrations (25,50,75 and 100)% were used to determine the effect and inhibition activity against 4 species of bacteria were isolated from the different sites of the human body's infection included Urinary tract Infection (UTI) ,skin infections (pus), and from stool (diarrhea), these bacteria were (Staphylococcus aureus ,Salmonella sp. , Klebsiella pneumonia and E. coli) and compared with inhibitory effect of some antibiotic discs (Trimethoprim/Sulfamethaxazole (25 µg), Ciprofloxacin 10 µg, Vancomycin (30µg), Norfloxacin (10 µg), and Lincomycin (15µg). Salmonella sp. most affected by gum Arabic with an inhibition rate of 10, while with kiwi fruits the inhibition rate was 8 compared to the used antibiotics, which showed resistance to it. The Minimum Inhibitory concentration (MIC) of gum Arabic against all bacterial species was at 10%, while MIC of kiwi fruit solution was at 25%. Minimum Inhibitory Concentration (MIC) of gum Arabic against bacterial isolates was 10% and 25% of kiwi fruit.30% of gum Arabic showed highest inhibition activity toward Klebsiella pneumoniae and E. coli at 15 and 10 mm but 50% of it showed highest activity toward Salmonella sp and Staphylococcus aureus at 12 and 16mm, 75% and 100% of Kiwi fruit juice was more effective against Klebsiella pneumoniae and E. coli at same measure inhibition zone at 9mm but Salmonella sp and Staphylococcus aureus were more affected by 75% Kiwi fruit juice at 11 and 12 mm respectively compared with other concentrations. The synergism effect of Gum Arabic (10 µg/ml) with Trimethoprim (25 µg/ml) was more effected against E. coli, the inhibition zone was at 12mm and Staphylococcus aureus was at 30mm, E. coli was resistant to Gum Arabic (10 µg/ml) and Triethoprime (25µg/ml) each of one alone, but Staphylococcus aureus bacteria the inhibition zone was at 9mm when treated with Gum Arabic (10 µg/ml) and resistant to Triethoprime (25µg/ml). in the same time Klebsiella pneumoniae and Salmonella sp. not affected with this synergism and Triethoprime (25µg/ml) aone, but they affected with Gum Arabic Acacia Senegal (10 µg/ml), the inhibition zones were 11 and 10 mm respectively.